The Content Variation of Four Active Components in Amygdalus persica L. during Different Harvesting Periods - Juanjuan Zhang; Xudong Chen; Zhenhua Yin; Qinfeng Guo; Baocheng Yang; Miaoqing Feng; Xiao Li; Lin Chen; Wei Zhang; Wenyi Kang (Journal of Food Quality)
In this study, a quantitative method for the content determination of rutin, 5-O-coumaroylquinic acid methyl ester, chlorogenic acid butyl ester, and kaempferol in Amygdalus persica L. flowers during different harvest periods was established to investigate its various rules and determine the optimal harvesting period. The determination was performed on the XTERRA MS C18 column with a mobile phase consisting of 0.1% formic acid aqueous solution and acetonitrile (gradient elution) at a flow rate of 1.0 mL/min. In combination with other validation data, including precision, stability, and recovery tests, this method demonstrated good reliability and sensitivity. The results showed that the contents of rutin, 5-O-coumaroylquinic acid methyl ester, chlorogenic acid butyl ester, and kaempferol in A. persica flowers during different harvest periods were quite different, and the content in samples at the early blooming stage was the highest. The method is simple, accurate, and rapid for determining the contents of four active ingredients in A. persica flowers.